Atomistic Modeling of Gas Adsorption in Nanocarbons. (12th December 2012) - Zollo, G.; Gala, F.
Abstract : Carbon nanostructures are currently under investigation as possible ideal media for gas storage and mesoporous materials for gas sensors. The recent scientific literature concerning gas adsorption in nanocarbons, however, is affected by a significant variation in the experimental data, mainly due to the different characteristics of the investigated samples arising from the variety of the synthesis techniques used and their reproducibility. Atomistic simulations have turned out to be sometimes crucial to study the properties of these systems in order to support the experiments, to indicate the physical limits inherent in the investigated structures, and to suggest possible new routes for application purposes. In consideration of the extent of the theme, we have chosen to treat in this paper the results obtained within some of the most popular atomistic theoretical frameworks without any purpose of completeness. A significant part of this paper is dedicated to the hydrogen adsorption on C-based nanostructures for its obvious importance and the exceptional efforts devoted to it by the scientific community.